Melatonin protects bone marrow mesenchymal stem cells against iron overload‐induced aberrant differentiation and senescence. Issue 3 (20th June 2017) - Yang, Fan; Yang, Lei; Li, Yuan; Yan, Gege; Feng, Chao; Liu, Tianyi; Gong, Rui; Yuan, Ye; Wang, Ning; Idiiatullina, Elina; Bikkuzin, Timur; Pavlov, Valentin; et al.
Abstract: Bone marrow mesenchymal stem cells (BMSCs) are an expandable population of stem cells which can differentiate into osteoblasts, chondrocytes and adipocytes. Dysfunction of BMSCs in response to pathological stimuli contributes to bone diseases. Melatonin, a hormone secreted from pineal gland, has been proved to be an important mediator in bone formation and mineralization. The aim of this study was to investigate whether melatonin protected against iron overload‐induced dysfunction of BMSCs and its underlying mechanisms. Here, we found that iron overload induced by ferric ammonium citrate (FAC) caused irregularly morphological changes and markedly reduced the viability in BMSCs. Consistently, osteogenic differentiation of BMSCs was significantly inhibited by iron overload, but melatonin treatment rescued osteogenic differentiation of BMSCs. Furthermore, exposure to FAC led to the senescence in BMSCs, which was attenuated by melatonin as well. Meanwhile, melatonin was able to counter the reduction in cell proliferation by iron overload in BMSCs. In addition, protective effects of melatonin on iron overload‐induced dysfunction of BMSCs were abolished by its inhibitor luzindole. Also, melatonin protected BMSCs against iron overload‐induced ROS accumulation and membrane potential depolarization. Further study uncovered that melatonin inhibited the upregulation of p53, ERK and p38 protein expressions in BMSCs with iron overload. Collectively, melatonin plays a protective role in iron overload‐induced osteogenic differentiation dysfunction and senescence through blocking ROS accumulation and p53/ERK/p38 activation.